A NEW APPROACH TO DEVELOPING THE PROFESSIONAL COMPETENCES OF FUTURE ENGINEERS THROUGH INTERACTIVE METHODS (Multidisciplinary Journal of Science and Technology, 2024)
This article is about the content and essence of professional competencies. Professional competencies and their specific characteristics. It is important to familiarize students of higher educational institutions with innovative educational technologies in various specialties, to increase their intellectual potential, to enrich their worldview, to improve their knowledge and skills in advanced courses.